Knowledge about the Origins of Uncertainties from the Pre-Project Phase of Road Projects - Rouzbeh Shabani; Olav Torp; Ole Jonny Klakegg; Agnar Johansen (Infrastructures, 2022)
To succeed with projects, we need to understand and manage uncertainty. Uncertainties impact a project’s cost, time, and quality performance. The project’s front end is challenging for decision makers due to the high level of uncertainty. This paper identifies the most common uncertainties and their origin in the pre-project phase of large road projects. It also analyses the changes in these factors over 20 years. Document studies collected information about uncertainty factors identified in the early phase of 90 large road projects. The research strategy was explanatory, and data were collected from quality assurance reports from a population of large Norwegian road projects. The project cost varies between USD 30 million and over USD 2 billion. Then, 15-factor groups were established for categorising uncertainties. This study shows a rise in uncertainty factors with operational origins and a decrease in uncertainty factors with strategic and contextual origins over the last 20 years. Identifying and understanding common uncertainties and their origins provides policymakers, practitioners, and researchers with useful insights for policy revision and investment decision making and facilitates a proper focus regarding uncertainty analyses in the front end of road projects.